Experimental Writing, Experimental Reading - Warren Motte (Studies in 20th & 21st Century Literature, 2018)
The notion of "experimental writing" is difficult to define with any kind of precision. Most of the time it is invoked in a largely offhanded manner, as if its meaning were immediately clear to everyone, obviating the need for further discussion. That assumption is a matter of expediency rather than anything else, for even a cursory glance at the way people use the term quickly reveals that the way we understand it varies considerably, changing over both time and cultural space. This essay seeks to examine how the idea of the experimental expresses itself in the tradition of the twentieth-century French avant-garde.
Keywords: experimental literature; avant-garde; reading